Implementasi Revolusi Mental melalui Instagram: Analisis Strategi Kehumasan Kemenko Pembangunan Manusia dan Kebudayaan RI - Yunilia Edon; Syarifuddin Gassing; Ilona V. Oisina S (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2026)
This study aims to analyze public relations strategies in the implementation of the Mental Revolution Program through Instagram at the Coordinating Ministry for Human Development and Cultural Affairs of the Republic of Indonesia. The Mental Revolution represents an effort to transform public mindsets, attitudes, and behaviors based on the values of integrity, work ethic, and mutual cooperation in order to build a progressive and competitive nation. This research employs a descriptive qualitative approach with a case study method. Data were collected through observation, in-depth interviews, documentation, and triangulation to ensure comprehensive findings. The results indicate that the implemented public relations strategies have optimally utilized social media as a means of public communication, particularly in reaching younger audiences. These strategies include the development of positive content, cross-sector collaboration, and the use of media relations to expand information dissemination. The SWOT analysis reveals that the main strengths lie in effective team coordination, structured communication strategies, and a strong organizational culture, while weaknesses include limited human resources and insufficient technological support. Opportunities arise from extensive networks with various institutions and media, whereas threats stem from public perceptions and limited communication competencies. In practice, the Mental Revolution Program is implemented participatively through various initiatives such as Indonesia Serving, Clean, Orderly, Independent, and United, which are disseminated via Instagram. However, its implementation has not been evenly distributed across regions and has only reached approximately 70%, due to budget constraints and varying levels of commitment among local governments. Therefore, the success of this program largely depends on synergy among stakeholders and consistency in internalizing transformative values within society.